Directive speech acts in the school slogans - Mubarok, Yasir; Anggraeni, Dhea Nur; Sugiyo, Sugiyo (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The purpose of the research is to identify directive illocutionary acts in school slogans. This study aims to investigate several categories of directive illocutionary speech acts in the school slogans at MTS Negeri 3 Tangerang. The method used by researchers is qualitative descriptive methods by referring to Searle's speech acts theory. The results showed that three kinds of directive speech acts are utilized in the school slogans; advising twenty utterances, commanding one utterance, requesting two utterances. Based on the results, the most dominant type of directive speech acts used was advising with 20 occurrences. It means that the school provides a lot of advice to their students (addressee) through these school slogans. In addition, context and co-context have a very important role in understanding the slogans thus the slogan found contains more to the philosophy of life and educational values.